Morphological Analysis of White Cement Clinker Minerals: Discussion on the Crystallization-Related Defects - Mohamed Benmohamed; Rabah Alouani; Amel Jmayai; Abdesslem Ben Haj Amara; Hafsia Ben Rhaiem (International Journal of Analytical Chemistry)
The paper deals with a formation of artificial rock (clinker). Temperature plays the capital role in the manufacturing process. So, it is useful to analyze a poor clinker to identify the different phases and defects associated with their crystallization. X-ray fluorescence spectroscopy was used to determine the clinker’s chemical composition. The amounts of the mineralogical phases are measured by quantitative XRD analysis (Rietveld). Scanning electron microscopy (SEM) was used to characterize the main phases of white Portland cement clinker and the defects associated with the formation of clinker mineral elements. The results of a study which focused on the identification of white clinker minerals and defects detected in these noncomplying clinkers such as fluctuation of the amount of the main phases (alite (C3S) and belite (C2S)), excess of the free lime, occurrence of C3S polymorphs, and occurrence of moderately-crystallized structures are presented in this paper.